Environmental contamination with persistent cyclic mustard gas impurities and transformation products. Issue 1 (1st January 2019) - Chmielińska, Katarzyna; Hubé, Daniel; Bausinger, Tobias; Simon, Markus; Rivière, Gilles; Fauser, Patrik; Sanderson, Hans
ABSTRACT: The battlefield of Verdun has seen some of the heaviest shelling in the history of mankind. This site as well as clean-up facilities in Germany may constitute contamination hot-spots and point-sources with leaking to groundwater. This study collected existing toxicological and ecotoxicological data on mustard gas degradation products, together with physical – chemical properties of listed compounds. It also provides quantities of these products measured in the groundwater of France, Germany and the pore water of the Baltic Sea. We indicate a deficiency of information on the toxicity of 1-oxa-4, 5-dithiepane and 1, 2, 5 – trithiepane. In the groundwater of the German city of Munster 1-oxa-4, 5-dithiepane was measured up to 250 µg/L, thus exceeding safe levels. Ecotoxicological studies classify this compound as toxic to aquatic organisms. 1, 2, 5-trithiepane is not a persistent compound. It was measured, however, in the groundwater at 1 µg/L level. This suggests that it could be formed from an active source of mustard gas. Considering the lack of toxicological data and the uncertainty about the amount of munition deposits, we suggest that research into the toxicity and exposure of, 1-oxa-4, 5-dithiepane and 1, 2, 5 – trithiepane is needed for sites of concern.